Pengaplikasian Teknologi Multimedia Dalam Teater “Bukan Bunuh Diri” - Hasniza, binti Abdul Halim (Universiti Malaysia Sarawak (UNIMAS), 2007)
The application of multimedia in amateur theatre is infrequently being applied in the theater performance. In this research the researcher tries to apply multimedia element into theater performance of “Bukan Bunuh Diri”. The purpose of the research is to evaluate the perspective in theatre field and also to identify how this approach can be use to help the director enlighten the plot and massage of theater to the audience.